The Role of Sukuk in Infrastructure Development: A Systematic Review of Global Experiences and Lessons Learned - Zuhri, Saifuddin; Fadil, Cholid (Penelitian dan Pengembangan Ilmu, 2024)
This research systematically examines the role of sukuk in infrastructure financing, with a focus on the lessons that can be learned from advanced Islamic financial markets and the implications for developing countries. Sukuk, as a financial instrument that complies with sharia principles, has been widely used in countries such as Malaysia, the United Arab Emirates (UAE), and Saudi Arabia to fund large-scale infrastructure projects. These countries have succeeded in developing strong regulatory frameworks, innovative sukuk structures, and broad investor participation. However, replicating this model in developing countries still faces challenges, such as political instability, low financial literacy, and immature legal infrastructure. Through a systematic literature review, this research identifies key factors that contribute to the success of sukuk in more developed markets and outlines the obstacles faced by developing countries. Additionally, this research provides practical recommendations for policymakers in developing countries, emphasizing the importance of a supportive regulatory environment, capacity development, and public-private partnerships (PPPs). The findings show that with appropriate adaptation, sukuk can be a viable solution for sustainable infrastructure development in developing countries. Future research is recommended to focus on empirical studies evaluating the effectiveness of sukuk in these countries as well as comparative analysis between different financial markets.